The role of information service in rational pharmacotherapy with thioctic acid in patients in Preferential Medicinal Providing - E. V. Eliseeva; E. S. Maneeva; V. V. Gribova; D. B. Okun; D. V. Savitskaya (Izdatelstvo OKI, 2021)
Rational pharmacotherapy in the Program of Preferential Medicinal Providing can be implemented subject to high-quality information support from healthcare professionals. Thioctic (Alpha-lipoic) Acid preparations are widely used in the preferential segment, their appointment is not always advisable due to the frequent use «off-label», which leads to ineffective treatment and unreasonable economic costs. Aim. Conduct an information search and filling the electronic service «Database of Clinical Trials of Medicines» for medicinal products containing Thioctic (Alpha-lipoic) Acid and provide author's recommendations for rational pharmacotherapy. Materials and methods. The search and analysis of the results of clinical trials, systematic reviews and meta-analysis in international and Russian Databases - PubMed, EMBASE, Cochrane Collaboration, e-Library, «Cyberlininka» for medicines of metabolic action - Thioctic (Alpha-lipoic) Acid with their subsequent introduction into the Information Service «Database of Clinical Trials of Medicines». Results. Thioctic (Alpha-lipoic) Acid has a positive effect in the form of improvement of the clinical condition of patients and indicators of neurological scales in diabetic and alcoholic polyneuropathy without affecting the «hard» endpoints (decrease in the number of fatal complications and mortality). Conclusion. Service «Database of Clinical Trials of Medicines» for use by health care professionals and the author's recommendations for the use of Thioctic (Alpha-lipoic) Acid can be used for the rational prescription of this medicines in Preferential Medicinal Providing.